Perpendicular and In‐Plane Conductivity of Poly(methyl methacrylate) Composite Films Filled with Carbon‐Based Fillers Prepared from Solution Casting Process - Xu, Huagen; Schubert, Dirk W. (Macromolecular Materials and Engineering, 2020)
In this study, poly(methyl methacrylate) (PMMA)/carbon black (CB), PMMA/carbon fiber (CF), and PMMA/carbon nanotube (CNT) conductive composite films with different filler concentrations are prepared using the solution casting technique. Both perpendicular and in‐plane direction conductivity of all the binary composite films are investigated, percolation thresholds (ϕc) of both directions of PMMA/CB, PMMA/CF, and PMMA/CNT composite films are investigated and the experimental data are fitted using McLachlan’s equation. For all the three investigated films, the perpendicular ϕc,⊥ and in‐plane ϕc,∥ with different fillers show totally different behaviors. Pristine CB, CF, and CNT as well as PMMA/CB, PMMA/CF, and PMMA/CNT composite films are discussed. The gravity effect of the fillers is found to be most significant in the PMMA/CB system. A schematic diagram of PMMA composite films with CB, CF, and CNT as filler prepared from solution casting process is presented to explain the distribution gradient of the fillers in the perpendicular direction of the film after solution casting. A power law behavior is revealed for different filler types (CB, CF, CNT) correlating the exponent t for McLachlan’s equation and corresponding ϕc for in‐plane and perpendicular direction
Keywords: carbon nanotubes; carbon black; carbon fillers; conductive polymer films; percolation threshold